PSYCHOLOGICAL ASPECTS OF SHARES AND DISCOUNTS IN DIGITAL MARKETING - Yanchuk, Tetiana; Kurylenko, Yu. (SWorld-Ger Conference proceedings, 2024)
The paper considers the psychological aspects of promotions and discounts in digital marketing. The key mechanisms that affect consumers, in particular the effect of scarcity, urgency and social confirmation, have been identified. Modern tools and methods